Doped chiral glasses with sub-minute adjustable afterglow and multi-optical applications
Patent Information
- Application Number
- CN202512057202.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-31
- Publication Date
- 2026-10-23
AI Technical Summary
因此,实现高 glum值、精确光致变色和小时级的余辉仍是一个未解决的挑战,目前还没有任何技术能够同时满足这些标准
(1)这类具有小时级以上的余辉材料,可以低温制备,且无需依赖希贵金属,相比于传统的需要1000℃合成条件纯无机长余辉材料,显著的降低能耗和提高生产安全性的特点。
Smart Images

Figure CN122959017A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of optical materials and new material technology development, specifically involving an organic-inorganic hybrid glass with ultra-long afterglow, photochromism and efficient circularly polarized light emission, its preparation method, and its applications in information storage, security, ultraviolet printing, polarized optical devices, high-strength and high-transparency components. Background Technology
[0002] Persistent emission (PersL) is an intriguing optical phenomenon characterized by an afterglow that can last from seconds to days after excitation ceases. Its potential in sensors, bioimaging, illumination, and information encryption has attracted widespread attention. Since the 1990s, artificial SrAl₂O₄:Eu... 2+ ,Dy 3+ The development of phosphors has greatly promoted the research and development of inorganic long-afterglow materials (such as metal oxides doped with rare earth ions). For example, US Patent No. 20220204838 applies long-afterglow materials to the field of information security. Therefore, long-afterglow materials are also experiencing a new boom. For instance, patent CN108585853A discloses a europium-doped scandium oxide afterglow material (Sc). 1-x-y M x Eu y Rare earth elements ()₂O₃ require conditions such as pressure (180–220) MPa and sintering temperature (1600–1700) °C to prepare. It can be seen that their synthesis conditions are harsh, typically requiring high-temperature synthesis and dependence on expensive rare earth elements. Furthermore, they often appear in powder and crystalline solid forms, necessitating the use of other mediators for large-scale applications, which is detrimental to energy conservation, emission reduction, and economic transformation. As a new generation of long afterglow materials, their synthesis conditions are mild, they are rare earth-free, and they can be adapted for large-scale preparation, making them a material urgently needed for development in the industry.
[0003] As a material with significant potential in optoelectronic and bioelectronic applications, circularly polarized long-afterglow materials show great promise for applications in 3D displays, bioimaging, high-throughput data storage, and photochemical synthesis. Most reported optical asymmetry factors (g...) lum The value is 10 -4 Up to 10 -3 Between. Furthermore, photochromic materials show promising applications in areas such as molecular switches and ultraviolet printing. Therefore, achieving high g... lumAchieving optimal photochromic properties, precise photochromism, and hour-long afterglow remains an unsolved challenge; no technology currently meets all these criteria simultaneously. Molecular-based hybrid glasses, as the fourth type of glass in glass chemistry and materials science, offer new possibilities beyond the manufacturing limitations and performance constraints of traditional inorganic (non-metallic), organic, and metallic systems. Currently, key advancements in this field lie in integrating multifunctionality into a single glass system, which is crucial for next-generation smart optical displays and information storage.
[0004] This patent aims to develop an organic-inorganic hybrid glass with ultra-long afterglow, photochromism, and efficient circularly polarized luminescence, making it promising for applications in information storage, security, ultraviolet printing, polarized optics, and high-strength, high-transmittance devices. We utilize R1~R6 and... R,R or S,S Doping (PTP)₂ZnBr₄, (ETP)₂ZnBr₄, and (ETP)₂CdBr₄ glasses with guest organic molecules creates host-guest glasses. The design concept for these metamaterials involves donor molecules undergoing charge transfer, forming stable free radicals that maintain a continuous charge-separated state. These free radicals overcome relatively small energy barriers and recombine with excitons, achieving hour-long afterglow and photochromic properties. Further doping introduces chiral organic compounds, enabling the hybrid glass to integrate circularly polarized luminescence. This patent, guided by ultra-long afterglow, precise photochromism, and efficient circularly polarized luminescence, constructs a class of hybrid glasses based on a host-guest doping strategy for application in advanced luminescent materials and photonics technologies. Summary of the Invention
[0005] The purpose of this invention is to provide an organic-inorganic hybrid glass with ultra-long afterglow, photochromism and efficient circularly polarized light emission, a preparation method, and applications in information storage, security, ultraviolet printing, polarized optical devices, high-strength and high-transparency components, etc., providing new ideas and feasible solutions for the design and synthesis of materials in the fields of novel advanced light emission and optical technology.
[0006] To facilitate patent drafting and use, this patent uses abbreviations for the following chemical substances and describes them in the format specified in parentheses before the CAS identifier, where Chemical Abstracts Service (CAS) is the unique identifier for international chemical substance allocation. Propyltriphenylphosphine bromide (PTP) CAS: 6228-47-3; Ethyltriphenylphosphine bromide (ETP) CAS: 1530-32-1; Zinc bromide (ZnBr2) CAS: 7699-45-8; Cadmium bromide (CdBr2) CAS: 7789-42-6; 4,4',4''-Trimethyltriphenylamine (R1) CAS: 1159-53-1; Tetra-N-phenyl-p-phenylenediamine (R2) CAS: 14118-16-2; N,N'-Diphenyl-N,N'-Di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (R3) CAS: 65181-78-4; N,N,N',N'-Tetra(4-tolyl)-1,1'-biphenyl-4,4'-diamine (R4) CAS: 76185-65-4; N,N-phenyl-N,N-(9-phenyl-3-carbazolyl)-1,1'-biphenyl-4,4'-diamine (R5) CAS: 887402-92-8; N,N',N''-tris(3-methylphenyl)-N,N',N''-triphenyl-1,3,5-phenyltriamine (R6) CAS: 138143-23-4; (1R,2R)-1,2-diphenylethylenediamine ( R,R CAS: 35132-20-8; (1S,2S)-1,2-diphenylethylenediamine S,S CAS: 29841-69-8. This invention utilizes R1~R6 and R,R or S,S Guest molecules were used to dope (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 glasses by means of optimized melt quenching and molecular doping strategies to form multifunctional hybrid glasses.
[0007] The specific preparation process of the complex described in this invention is as follows: (1) Propyltriphenylphosphine bromide or ethyltriphenylphosphine bromide is dissolved in ZnBr2 or CdBr2 at a molar ratio of 2:1 in an all-acetonitrile or a mixed solvent with a volume ratio of acetonitrile:dichloromethane of 3:1 and slowly evaporated to obtain (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 crystals.
[0008] (2) The (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 crystals are placed in a mold and heated to 160~230℃ to melt them completely. They are then rapidly cooled to room temperature to obtain the (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 hybrid glass of the present invention.
[0009] (3) The crystal obtained in step (1) is mixed with R1, R2, R3, R4, R5 or R6 in a molar ratio of 0 to 30%, placed in a mold, heated to 200 to 230°C until completely melted, and then rapidly cooled to room temperature to obtain the hybrid glass of the present invention: for example: (PTP)2ZnBr4@ x %R(1) ( x = 0–30%), (PTP)2ZnBr4@ x %R(2) ( x = 0–30%),(PTP)2ZnBr4@ x %R(3) ( x = 0–30%),(PTP)2ZnBr4@ x %R(4) ( x = 0–30%),(PTP)2ZnBr4@ x %R(5)( x = 0–30%), (PTP)2ZnBr4@ x %R(6) ( x = 0–30%); (ETP)2ZnBr4@ x %R(1) ( x = 0–30%),(ETP)2ZnBr4@ x %R(2) ( x = 0–30%),(ETP)2ZnBr4@ x %R(3) ( x = 0–30%),(ETP)2ZnBr4@ x %R(4) ( x =0–30%),(ETP)2ZnBr4@ x %R(5) ( x = 0–30%),(ETP)2ZnBr4@ x %R(6) ( x = 0–30%),(ETP)2CdBr4@ x %R(1) ( x = 0–30%).
[0010] (4) The crystal obtained in step (1) is reacted with R1, R2, R3, R4, R5 or R6 in a molar ratio of 0-30%, and then a different amount of [unspecified ingredient] is added in a molar ratio of 0-30%. R,R or S,S Mix thoroughly, place in a mold, heat to 160~230℃ until completely melted, and rapidly cool to room temperature to obtain the hybrid glass of this invention: for example (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %S,S ( y = 0–30%), (ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%).
[0011] (5) Alternatively, a rapid preparation method can be used, such as adding 0-30% of R1, R2, R3, R4, R5, or R6 to ZnBr2 or CdBr2 at a molar ratio of 2:1. If preparing circularly polarized glass, an additional 0-30% of [the following ingredient] can be added. R,R or S,S The solvent is dissolved in acetonitrile or a mixed solvent with a volume ratio of acetonitrile / dichloromethane of 3:1. The solvent is then evaporated at a temperature greater than 70°C to obtain a mixed solid.
[0012] (6) Propyltriphenylphosphine bromide or ethyltriphenylphosphine bromide is dissolved in ZnBr2 or CdBr2 at a molar ratio of 2:1 in an acetonitrile or acetonitrile / dichloromethane mixed solvent at a volume ratio of 3:1. The solvent is evaporated to dryness at a temperature greater than 70°C to obtain a mixed solid. The mixed solid is placed in a mold and melted completely, then rapidly cooled to room temperature to obtain the (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 hybrid glasses of the present invention.
[0013] (7) Place the mixed solid obtained in (5) in a mold, heat it to 160~230℃ to melt it completely, and quickly cool it to room temperature to obtain the hybrid glass of the present invention: for example: (PTP)2ZnBr4@ x %R(1) (x = 0–30%), (PTP)2ZnBr4@ x %R(2) ( x = 0–30%),(PTP)2ZnBr4@ x %R(3) ( x = 0–30%),(PTP)2ZnBr4@ x %R(4) ( x =0–30%),(PTP)2ZnBr4@ x %R(5) ( x = 0–30%), (PTP)2ZnBr4@ x %R(6) ( x = 0–30%); (ETP)2ZnBr4@ x %R(1) ( x = 0–30%),(ETP)2ZnBr4@ x %R(2) ( x = 0–30%),(ETP)2ZnBr4@ x %R(3) ( x =0–30%),(ETP)2ZnBr4@ x %R(4) ( x = 0–30%),(ETP)2ZnBr4@ x %R(5) ( x = 0–30%),(ETP)2ZnBr4@ x %R(6) ( x = 0–30%),(ETP)2CdBr4@ x %R(1),(PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%),(PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%),(PTP)2ZnBr4@20%R(1)+ y %S,S ( y =0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%)。
[0014] (8) The hybrid glass obtained according to (3), (4) and (7) exhibits the property of a long afterglow in the hours after the ultraviolet lamp is turned off.
[0015] (9) The long afterglow color of the hybrid glass obtained according to (3), (4) and (7) can be adjusted according to the types of guest molecules R1, R2, R3, R4, R5 or R6.
[0016] (10) The hybrid glass obtained according to (3), (4) and (7) exhibits precise photochromic behavior.
[0017] (11) Circularly polarized hybrid glass obtained according to (4) and (7): for example (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %S,S ( y =0–30%), (ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%) exhibits circularly polarized luminescence characteristics.
[0018] (12) The (PTP)₂ZnBr₄ and (ETP)₂ZnBr₄ glasses obtained according to (2) and (6) exhibit high strength and high transmittance, with Young's moduli of 9.37 GPa and 8.13 GPa, respectively, and hardnesses of 432 ± 46.24 MPa and 349 ± 3.2 MPa, respectively. Among them, (PTP)₂ZnBr₄ has extremely high optical transmittance, exceeding 85% in the 580-700 nm wavelength range and reaching 94% in the 700-1000 nm wavelength range.
[0019] The materials prepared above were characterized as follows: 1. X-ray single-crystal diffraction data show that the obtained (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 crystals all have typical A2BX4 structures and belong to the P21 or P21 / n space group crystals. They form 0D structures through CH—Br, CH—π hydrogen bonds, van der Waals forces and π—π.
[0020] 2. Differential thermal analysis (DSC) showed the glass-forming ability (GFA = T) of all the hybrid glasses obtained. g / T m A value between 2 / 3 and 1 indicates a strong tendency to form glass.
[0021] 3. The X-ray diffraction (XRD) pattern showed broad scattering peaks, which confirmed the long-range disordered amorphous properties of all the hybrid glasses obtained.
[0022] 4. The optical properties of the hybrid glass were investigated using steady-state photoluminescence (PL), steady-state delayed spectroscopy (LPL), and luminescence decay curve measurements. (PTP)2ZnBr4@ x %R(1) ( x = 2–20%) and (PTP)2ZnBr4@ x %R(2) ( x =2–15%) exhibits broad PL and LPL emission bands under 395 nm excitation, with peaks at approximately 526 nm and 550 nm, respectively. (PTP)2ZnBr4@ x %R(3) ( x = 2–15%) and (PTP)2ZnBr4@ x %R(4) ( x The emission peaks of ( = 2–15%) are approximately at 558 nm and 564 nm. (PTP)2ZnBr4@ x %R(5) ( x = 0–30%) and (PTP)2ZnBr4@ x %R(6) ( x = 0–30%) LPL peaks exist at 568 nm and 530 nm, respectively. Their afterglow durations both exceed 1.25 hours. Similarly, the LPL peaks of the simplified description (ETP)2ZnBr4@R(n) (n = 1 – 6) glass are all located above 500 nm, and their afterglow lifetimes are all longer than 1.25 hours.
[0023] 5. The obtained hybrid glasses exhibited photochromism, and transmittance analysis was performed on some samples. After exposure to a 395 nm LED light source for 60 s, (PTP)₂ZnBr₄@20%R₁ changed from transparent light yellow to dark blue, while (PTP)₂ZnBr₄@15%R₂ changed from transparent to light green. Similarly, (PTP)₂ZnBr₄@15%R₃, (PTP)₂ZnBr₄@15%R₄, (PTP)₂ZnBr₄@10%R₅, and (PTP)₂ZnBr₄@10%R₆ gradually changed from yellow to dark brown. Ultraviolet-visible-near-infrared (UV-vis-NIR) transmission spectroscopy further verified these photochromic properties. (PTP)₂ZnBr₄@20%R₁ exhibits a significant decrease in transmittance in the 450–800 nm range, while (PTP)₂ZnBr₄@15%R₂ shows a similar decrease in transmittance in the 500–1200 nm range, consistent with the observed color change. For (PTP)₂ZnBr₄@15%R₃, (PTP)₂ZnBr₄@15%R₄, (PTP)₂ZnBr₄@10%R₅, and (PTP)₂ZnBr₄@10%R₆, two distinct transmittance decreases were observed: one in the 580–800 nm range, corresponding to a brownish-yellow hue; and another in the near-infrared (NIR) region (800–2000 nm).
[0024] 6. Circular dichroism (CD) spectra show mirror images, with R,R-doped glasses exhibiting positive CD signals and S,S-doped glasses showing negative signals. CD signals above 450 nm correspond to absorption spectra. Furthermore, R,R- and S,S-doped (PTP)₂ZnBr₄@R₁ glasses exhibit strong CPL at 510 nm, possessing high |g lum | Value 1.1 × 10 -2 The R,R- and S,S- doped (ETP)₂CdBr₄@R₁ glass exhibits strong CPL at 550 nm, |g lum The value is 3.8 × 10 -3 .
[0025] Advantages of this invention: (1) This type of afterglow material with an afterglow of more than one hour can be prepared at low temperature and does not rely on rare precious metals. Compared with traditional pure inorganic long afterglow materials that require synthesis conditions of 1000℃, it has the characteristics of significantly reducing energy consumption and improving production safety.
[0026] (2) Traditional long afterglow materials often appear in the form of powder and crystalline solid. The hybrid glass prepared by the present invention can be prepared freely in a green and large size, and has high processability. Moreover, the morphology can be adjusted according to the mold.
[0027] (3) The hybrid glass prepared exhibits a long afterglow on the order of hours, which is far superior to traditional organic or organic-inorganic hybrid materials.
[0028] (4) The obtained hybrid glass material exhibits precise photochromic properties under ultraviolet light irradiation.
[0029] (5) The obtained hybrid glass material exhibits circularly polarized light emission characteristics.
[0030] (6) The obtained glass exhibits high strength and high transparency.
[0031] (7) The obtained hybrid glass material can be used in the fields of ultraviolet printing and other technologies. Attached Figure Description
[0032] Figure 1 (a) Organic ligand structure, (bd) Crystal structures of (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4.
[0033] Figure 2 (a) XRD powder diffraction pattern of (PTP)2ZnBr4@R1. (b) Fourier transform infrared (FTIR) spectrum of (PTP)2ZnBr4@R1. (ce) Glass forming ability (GFA) value of hybrid glass based on DSC data analysis.
[0034] Figure 3 (a) Transmittance analysis of (PTP)2ZnBr4 glass. (b) Nanoindentation test of (PTP)2ZnBr4 and (c) (ETP)2ZnBr4 glass, as well as Young's modulus and hardness analysis.
[0035] Figure 4 Afterglow lifetime decay curves of the luminescent center of (ad, gn) hybrid glass. PL and LPL spectra analysis of (PTP)2ZnBr4@R1 and (PTP)2ZnBr4@R2 glasses.
[0036] Figure 5 (a) The hybrid glass exhibits photochromism after 1 min of UV excitation, wherein the six hybrid glasses above are (PTP)2ZnBr4@R( n ) ( n =1-6) and the two hybrid glasses below are (PTP)2ZnBr4@R(1)+ R, Rand (PTP)2ZnBr4@R(1)+ S,S (b) (PTP)2ZnBr4@R(1) Transmittance analysis of glass before and after UV excitation for 1 min.
[0037] Figure 6 :(ab) (PTP)2ZnBr4@R(1)+ R,R and (PTP)2ZnBr4@R(1)+ S,S CPL spectrum of glass and g lum Figure. (cd) (PTP)2CdBr4@R(1)+ R,R and (PTP)2CdBr4@R(1)+ S,S CPL spectrum of glass and g lum picture.
[0038] Figure 7 :(ae) (PTP)2ZnBr4@R(1) Application of glass in ultraviolet printing and information storage as well as precise photochromism, in which glass is covered with a QR code template and then excited with ultraviolet light for 1 min. (fg) (PTP)2ZnBr4@20%R1 The processability of glass, using molten hybrid glass for direct writing. Detailed Implementation
[0039] The present invention will be further illustrated below by way of examples, but is not limited to these examples. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field. Unless otherwise specified, the reagents and materials used in the following examples are all commercially available. Example 1
[0040] (1) Phosphorus propyltriphenylbromide or phosphorus ethyltriphenylbromide ( Figure 1 (a) They were dissolved in acetonitrile or a mixed solvent of acetonitrile and dichloromethane in a molar ratio of 2:1, respectively, and slowly evaporated to obtain (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 crystals.
[0041] (2) The (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 crystals are placed in a mold and heated to 160~230℃ to melt them completely. They are then rapidly cooled to room temperature to obtain the (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 hybrid glass of the present invention.
[0042] (3) The crystal obtained in step (1) is mixed with R1, R2, R3, R4, R5 or R6 in a molar ratio of 0 to 30%, placed in a mold, heated to 200 to 230°C until completely melted, and then rapidly cooled to room temperature to obtain the hybrid glass of the present invention: for example: (PTP)2ZnBr4@ x %R(1), (PTP)2ZnBr4@ x %R(2),(PTP)2ZnBr4@ x %R(3),(PTP)2ZnBr4@ x %R(4),(PTP)2ZnBr4@ x %R(5), (PTP)2ZnBr4@ x %R(6), (ETP)2ZnBr4@ x %R(1),(ETP)2ZnBr4@ x %R(2), (ETP)2ZnBr4@ x %R(3),(ETP)2ZnBr4@ x %R(4),(ETP)2ZnBr4@ x %R(5),(ETP)2ZnBr4@ x %R(6),(ETP)2CdBr4@ x %R(1), ( x = 0–30%).
[0043] (4) The crystal obtained in step (1) is reacted with R1, R2, R3, R4, R5 or R6 in a molar ratio of 0-30%, and then a different amount of [unspecified ingredient] is added in a molar ratio of 0-30%. R,R or S,S Mix thoroughly, place in a mold, heat to 160~230℃ until completely melted, and rapidly cool to room temperature to obtain the hybrid glass of this invention: for example: (PTP)2ZnBr4@20%R(1)+ y %R,R,(PTP)2ZnBr4@20%R(1)+ y %R,R,(PTP)2ZnBr4@20%R(1)+ y %S,S,(ETP)2CdBr4@15%R(1)+ y %R,R,(ETP)2CdBr4@15%R(1)+ y %R,R, ( y = 0–30%).
[0044] (5) Alternatively, a rapid preparation method can be used, such as adding 0-30% of R1, R2, R3, R4, R5, or R6 to ZnBr2 or CdBr2 at a molar ratio of 2:1. If preparing circularly polarized glass, an additional 0-30% of [the following ingredient] can be added. R,R or S,S The solvent is dissolved in acetonitrile or a mixed solvent with a volume ratio of acetonitrile / dichloromethane of 3:1. The solvent is then evaporated at a temperature greater than 70°C to obtain a mixed solid.
[0045] (6) Propyltriphenylphosphine bromide or ethyltriphenylphosphine bromide is dissolved in ZnBr2 or CdBr2 at a molar ratio of 2:1 in an acetonitrile or acetonitrile / dichloromethane mixed solvent at a volume ratio of 3:1. The solvent is evaporated to dryness at a temperature greater than 70°C to obtain a mixed solid. The mixed solid is placed in a mold and melted completely, then rapidly cooled to room temperature to obtain the (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 hybrid glasses of the present invention.
[0046] (7) Place the mixed solid obtained in (5) in a mold, heat it to 160~230℃ to melt it completely, and quickly cool it to room temperature to obtain the hybrid glass of the present invention: for example: (PTP)2ZnBr4@ x %R(1), (PTP)2ZnBr4@ x %R(2),(PTP)2ZnBr4@ x %R(3),(PTP)2ZnBr4@ x %R(4),(PTP)2ZnBr4@ x %R(5), (PTP)2ZnBr4@ x %R(6), (ETP)2ZnBr4@ x %R(1), (ETP)2ZnBr4@ x %R(2), (ETP)2ZnBr4@ x %R(3),(ETP)2ZnBr4@ x %R(4),(ETP)2ZnBr4@ x %R(5),(ETP)2ZnBr4@ x %R(6),(ETP)2CdBr4@ x %R(1), ( x = 0–30%); (PTP)2ZnBr4@20%R(1)+ y %R,R,(PTP)2ZnBr4@20%R(1)+ y%R,R,(PTP)2ZnBr4@20%R(1)+ y %S,S,(ETP)2CdBr4@15%R(1)+ y %R,R, (ETP)2CdBr4@15%R(1)+ y %R,R, ( y = 0–30%).
[0047] (8) X-ray single-crystal diffraction data showed that the obtained (PTP)₂ZnBr₄, (ETP)₂ZnBr₄ and (ETP)₂CdBr₄ crystals ( Figure 1 (bc), they all have typical A2BX4 structures, belong to the P21 or P21 / n space group crystals, and they form 0D structures through CH—Br, CH—π hydrogen bonds, van der Waals forces and π—π.
[0048] (9) Differential thermal analysis (DSC) showed the glass-forming ability (GFA = T) of all the hybrid glasses obtained. g / T m The GFA values of all of them are between 2 / 3 and 1. Figure 2 (ce), indicating a strong tendency to form glass.
[0049] (10) The X-ray diffraction (XRD) pattern shows broad scattering peaks ( Figure 2 This confirms the long-range disordered amorphous properties of all the obtained hybrid glasses. Fourier transform infrared spectroscopy shows absorption bands at approximately 1270–1320 cm⁻¹ and 520–1115 cm⁻¹, corresponding to the stretching vibrations of Ar-N and Ar-P atoms, respectively. Figure 2 (b). These results confirm that the R1-R6 guest molecules were successfully integrated into the glass. Example 2
[0050] The obtained (PTP)₂ZnBr₄ and (ETP)₂ZnBr₄ glasses exhibited high strength and high transparency, with Young's moduli of 9.37 GPa and 8.13 GPa, respectively, and hardnesses of 432 ± 46.24 MPa and 349 ± 3.2 MPa, respectively. Figure 2 (bc). Among them, (PTP)₂ZnBr₄ has extremely high optical transmittance, exceeding 85% in the 580-700 nm wavelength range and reaching 94% in the 700-1000 nm wavelength range. Figure 2 ,a). Example 3
[0051] (PTP)2ZnBr4@ x%R(1) ( x = 2–20%) and (PTP)2ZnBr4@ x %R(2) ( x = 2–15%) exhibits broad PL and PersL emission bands under 395 nm excitation, with peaks at approximately 526 nm and 550 nm, respectively. (PTP)2ZnBr4@ x %R(3) ( x = 2–15%) and (PTP)2ZnBr4@ x %R(4) ( x The emission peaks of ( = 2–15%) are approximately at 558 nm and 564 nm. (PTP)2ZnBr4@ x %R(5) ( x = 0–30%) and (PTP)2ZnBr4@ x %R(6) ( x = 0–30%) LPL peaks exist at 568 nm and 530 nm, respectively. Their afterglow durations both exceed 1.25 hours. Similarly, the LPL peaks of the simplified description (ETP)2ZnBr4@R(n) (n = 1–6) glass are all located above 500 nm, and their afterglow lifetimes are all longer than 1.25 hours. Figure 4 ). Example 4
[0052] The obtained hybrid glasses exhibited photochromism, and transmittance analysis was performed on some samples. After exposure to a 395 nm LED light source for 60 s, (PTP)₂ZnBr₄@20%R₁ changed from a transparent light yellow to a deep blue (Fig. 5a), while (PTP)₂ZnBr₄@15%R₂ changed from transparent to light green (Fig. 5a). Similarly, (PTP)₂ZnBr₄@15%R₃, (PTP)₂ZnBr₄@15%R₄, (PTP)₂ZnBr₄@10%R₅, and (PTP)₂ZnBr₄@10%R₆ gradually changed from yellow to dark brown (Fig. 5a). UV-Vis-NIR transmission spectroscopy further confirmed these photochromic properties. (PTP)2ZnBr4@20%R1 exhibits a significant decrease in transmittance in the 450–800 nm range (Fig. 5b), while (PTP)2ZnBr4@15%R2 shows a similar decrease in transmittance in the 500–1200 nm range, consistent with the observed color change. For (PTP)2ZnBr4@15%R3, (PTP)2ZnBr4@15%R4, (PTP)2ZnBr4@10%R5, and (PTP)2ZnBr4@10%R6, two distinct transmittance decreases were observed: one in the 580–800 nm range, corresponding to a brownish-yellow color change (…). Figure 5 a); another is in the near-infrared (NIR) region (800 to 2000 nanometers). Example 5
[0053] Circular dichroism (CD) spectra showed mirror images, with R,R-doped glasses exhibiting positive CD signals and S,S-doped glasses showing negative signals. The CD signals above 450 nm corresponded to absorption spectra, confirming their intrinsic electronic origin. Furthermore, R,R- and S,S-doped (PTP)₂ZnBr₄@R₁ glasses exhibited strong CPL at 510 nm, possessing high |g lum | Value 1.1 × 10 -2 (Figures 6a-b), while R,R- and S,S- doped (ETP)2CdBr4@R1 glasses exhibit strong CPL at 550 nm, |g lum The value is 3.8 × 10 -3 (Figures 6c-d). Example 6
[0054] This patent presents a large-scale proof-of-concept glass for UV printing and information storage: (PTP)₂ZnBr₄@20%R₁ (5 cm × 6 cm) (2.5 cm × 2.5 cm). As shown in Figures 5a-b, a QR code template was placed on the (PTP)₂ZnBr₄@20%R₁ glass and irradiated with 395 nm LED light for 1 minute (Figure 7a), thus etching the QR code onto the glass. After removing the template, a green afterglow QR code appeared, which can be scanned with a smartphone to directly access the official website (Figures 7c, e). Notably, due to the material's precise photochromic reaction, the color-changing code remains visible under natural light (Figures 7d, e), demonstrating its dual function as a UV-printable information storage optics device.
[0055] This patent further investigates the processability of (PTP)₂ZnBr₄@20%R₁ glass, utilizing its low-temperature melting and quenching properties. Upon heating, it liquefies into a semiconductor ink, enabling the direct printing of Chinese characters such as "sun" (Fig. 7f) and "moon" (Fig. 7g). This demonstrates the high processability of hybrid glass.
Claims
1. A method for preparing a type of doped chiral glass with tunable afterglow on the order of hours, characterized in that, The preparation steps are as follows: 1) Propyltriphenylphosphine bromide or ethyltriphenylphosphine bromide is dissolved in acetonitrile or a mixed solvent with an acetonitrile:dichloromethane volume ratio of 3:1 at a molar ratio of 2:1 with ZnBr2 or CdBr2, and slowly evaporated to obtain (PTP)2ZnBr4, (ETP)2ZnBr4 and (ETP)2CdBr4 crystals; 2) The obtained crystals are mixed with 4,4',4''-trimethyltriphenylamine, tetra-N-phenyl-p-phenylenediamine, N,N'-diphenyl-N,N'-di(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N,N',N'-tetra(4-tolyl)-1,1'-biphenyl-4,4'-diamine, N,N-phenyl-N,N-(9-phenyl-3-carbazolyl)-1,1'-biphenyl-4,4'-diamine, and N,N',N''-tris(3-methylphenyl)-N,N',N''-triphenyl-1,3,5-phenyltriamine at a molar ratio of 0-30%, placed in a mold, and heated to 200-230°C until completely melted. The mixture is then rapidly cooled to room temperature to obtain the hybrid glass of this invention: for example, (PTP)2ZnBr4@ x %R(1) ( x = 0–30%), (PTP)2ZnBr4@ x %R(2) ( x = 0–30%),(PTP)2ZnBr4@ x %R(3) ( x = 0–30%),(PTP)2ZnBr4@ x %R(4) ( x = 0–30%),(PTP)2ZnBr4@ x %R(6) ( x = 0–30%); (ETP)2ZnBr4@ x %R(1) ( x = 0–30%),(ETP)2ZnBr4@ x %R(2) ( x = 0–30%),(ETP)2ZnBr4@ x %R(3) ( x = 0–30%),(ETP)2ZnBr4@ x %R(4) ( x = 0–30%),(ETP)2ZnBr4@ x %R(5) ( x = 0–30%),(ETP)2ZnBr4@ x %R(6) ( x = 0–30%),(ETP)2CdBr4@ x %R(1) ( x = 0–30%); 3) The obtained (PTP)₂ZnBr₄ and (ETP)₂CdBr₄ crystals were mixed with R₁-R₆ in a molar ratio of 0-30% and R₂-R₆ in a molar ratio of 0-30%. R,R or S,S Mix thoroughly, heat to 160~230℃ until completely melted, and rapidly cool to room temperature to obtain the hybrid glass of this invention: for example, (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %R,R( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %S,S ( y = 0–30%), (ETP)2CdBr4@15%R(1)+ y %R,R ( y =0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%); 4) Alternatively, a rapid preparation method can be used, such as adding 0-30% of R1-R6 to ZnBr2 or CdBr2 at a molar ratio of 2:1, either propyltriphenylphosphine bromide or ethyltriphenylphosphine bromide. If preparing circularly polarized glass, 0-30% of [the desired amount] can be added further. R,R or S,S The solvent is dissolved completely in acetonitrile or a mixed solvent with an acetonitrile / dichloromethane volume ratio of 3:
1. The solvent is then evaporated to dryness at a temperature above 70°C to obtain a mixed solid. The obtained solid is placed in a mold and heated to 160-230°C until completely melted. It is then rapidly cooled to room temperature to obtain the hybrid glass of this invention: for example, (PTP)₂ZnBr₄@ x %R(1) ( x = 0–30%), (PTP)2ZnBr4@ x %R(2) ( x = 0–30%),(PTP)2ZnBr4@ x %R(3) ( x = 0–30%),(PTP)2ZnBr4@ x %R(4) ( x = 0–30%),(PTP)2ZnBr4@ x %R(6) ( x = 0–30%); (ETP)2ZnBr4@ x %R(1) ( x = 0–30%),(ETP)2ZnBr4@ x %R(2) ( x = 0–30%),(ETP)2ZnBr4@ x %R(3) ( x = 0–30%),(ETP)2ZnBr4@ x %R(4) ( x = 0–30%),(ETP)2ZnBr4@ x %R(5) ( x = 0–30%),(ETP)2ZnBr4@ x %R(6) ( x = 0–30%),(ETP)2CdBr4@ x %R(1), (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%),(PTP)2ZnBr4@20%R(1)+ y %S,S ( y =0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%)。 2. The preparation method according to claim 1, characterized in that, The obtained (PTP)₂ZnBr₄, (ETP)₂ZnBr₄, and (ETP)₂CdBr₄ crystals have lattice groups P₂₁ or P₂₁ / n and consist of zero-dimensional tetrahedral [ZnBr₄]. 2- and [CdBr4] 2- It is formed by stacking organic ligands ETP or PTP in a 1:2 ratio.
3. The preparation method according to claim 1, characterized in that, The resulting hybrid glass: for example: (PTP)2ZnBr4@ x %R(1) ( x = 0–30%), (PTP)2ZnBr4@ x %R(2) ( x = 0–30%),(PTP)2ZnBr4@ x %R(3) ( x = 0–30%),(PTP)2ZnBr4@ x %R(4) ( x = 0–30%),(PTP)2ZnBr4@ x %R(6) ( x = 0–30%); (ETP)2ZnBr4@ x %R(1) ( x = 0–30%),(ETP)2ZnBr4@ x %R(2) ( x = 0–30%),(ETP)2ZnBr4@ x %R(3) ( x = 0–30%),(ETP)2ZnBr4@ x %R(4) ( x = 0–30%),(ETP)2ZnBr4@ x %R(5) ( x = 0–30%),(ETP)2ZnBr4@ x %R(6) ( x = 0–30%),(ETP)2CdBr4@ x %R(1), (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %S,S ( y =0–30%), (ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%) exhibits a long afterglow property on the order of hours after the UV lamp is turned off.
4. The preparation method according to claim 1, characterized in that, The obtained hybrid glass material exhibits photochromic properties under ultraviolet light irradiation.
5. The obtained hybrid glass (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %R,R ( y =0–30%), (PTP)2ZnBr4@20%R(1)+ y %S,S ( y =0–30%), (ETP)2CdBr4@15%R(1)+ y %R,R ( y =0–30%),(ETP)2CdBr4@15%R(1)+ y %R,R ( y = 0–30%) The material exhibits circularly polarized luminescence characteristics.
6. The obtained (PTP)₂ZnBr₄ and (ETP)₂ZnBr₄ glasses exhibit high strength and high transmittance, with Young's moduli of 9.37 GPa and 8.13 GPa, respectively, and hardnesses of 432 ± 46.24 MPa and 349 ± 3.2 MPa, respectively. Among them, (PTP)₂ZnBr₄ has extremely high optical transmittance, exceeding 85% in the 580–700 nm wavelength range and reaching 94% in the 700–1000 nm wavelength range.
7. The obtained hybrid glass material can be used in the fields of anti-counterfeiting, information storage and encryption.
8. The obtained hybrid glass material can be used in technical fields such as ultraviolet printing.
9. The obtained circularly polarized light-emitting hybrid glass material can be used in technical fields such as polarized light devices.
10. The obtained hybrid glass can be used in the field of high-strength and high-transparency materials.
Citation Information
Patent Citations
Europium-doped scandium oxide scintillator, preparation method and uses thereof
CN108585853A
Long-afterglow luminescent material
US20220204838A1